Recreational potential evaluation of the perspective national park «Lisova pisnia» - Andriy Shulgach; Mykhaylo Melniychuk (Časopis Socìalʹno-Ekonomìčnoï Geografìï. Часопис соціально-економічної географії)
The recreational potential of Turia and Stokhid middle watershed geosystem is studied. Historical and cultural, recreational and wellness, ecological environmental components of that potential are identified as significant factors of the National Park organization herein. Creation of new national parks and their delineation must be scientifically justified and conform to the requirements of the laws of Ukraine. Also an important criterion is the presence of national historical heritage and humanistic resource potential. The article stresses the need to preserve landscapes which became known worldwide thanks to the Lesya Ukrainka’s work. That landscapes with high recreational potential which forms totemic, sacred relation to the landscape as to the native land. Nechymne lake – the live scenery of the Lesya Ukrainka’s immortal piece, a cradle of the “Lisova pisnia”. Esthetic and recreational potential of Krychevytske, Mezhyliske and Povorske lakes, biotic diverse of landscape complexes which survived in the middle flow of Turiya and Stokhid are paid attention in the article.